Threat Analysis of Nipah Virus as a New Pandemic from the Perspective of Medical Intelligence - Firdaus Sirait; Armi Susandi; Budiman Bela (PT Mattawang Mediatama Solution, 2024)
According to World Health Organization (WHO), Nipah virus is a type of infectious disease from 10 types of infectious diseases that can pose a risk to the public health. Besides, it has the potential to become a new pandemic. The State Intelligence Agency has the authority, mandate, and responsibility to actively engage in early detection of a disease that could potentially become an epidemic and cause a threat to national security and interests. The formulation of this research problem is